Freeze-framing territory: time and its significance in land governance. Issue 2 (3rd May 2016) - Fisher, David
Abstract : This paper explores how temporal symbolism is used to construct land as an object of enduring value. Using anthropological and ethnographic sources, I highlight how different practices of landholding are informed by different understandings of "permanence". I elaborate on how institutions of landholding employ "temporal signposts" to mark out land allocation and access arrangements over time. In conclusion, I explore the political roles of inter-temporal land governance, positing a link between codified "permanences" of landholding in land laws and the entrenchment of socio-spatial power. I suggest that the temporal dimension of land governance demands interrogation alongside the spatial.